Circulating thyroid hormones and clinical parameters of heart failure in men - Iva Turić; Ivan Velat; Željko Bušić; Viktor Čulić (Scientific Reports, 2023)
Abstract Heart failure (HF) is a multiple hormonal deficiency syndrome which includes alterations in the serum concentration of thyroid hormones (TH). This cross-sectional study enrolled 215 male patients hospitalised for acute HF. Data on cardiovascular risk factors, chronic medications, cardiac function assessed by echocardiography, and clinical parameters of HF were prospectively collected. The independent predictive association of TH with all investigated parameters of the HF severity were assessed. The patient’s mean age was 74.4 years, 57.2% had arterial hypertension, 54.0% were consuming alcohol, and 42.3% were diabetics. Multivariate analysis revealed that total triiodothyronine (TT3) was an independent predictor of greater left ventricular ejection fraction (LVEF; β = 0.223, p = 0.008), less progressed left ventricular diastolic dysfunction (LVDD; β = − 0.271, p = 0.001) and lower N-terminal pro-brain natriuretic peptide (NT-proBNP; β = − 0.365, p < 0.001). None of the TH other than TT3 was associated with LVDD or NT-proBNP, whereas free triiodothyronine (β = − 0.197, p = 0.004), free thyroxine (β = − 0.223, p = 0.001) and total thyroxine (β = − 0.140, p = 0.041) were inversely associated with LVEF. The present study suggests that, among TH, serum TT3 level is most closely associated with echocardiographic, laboratory and clinical parameters of the severity of HF in men.